Molecular Entanglement Witness by Absorption Spectroscopy in Cavity QED - Wu, Weijun; Fassioli, Francesca; Huse, David A.; Scholes, Gregory D. (Journal of Physical Chemistry Letters, 2025)
Producing and maintaining molecular entanglement at room temperature and detecting multipartite entanglement features of macroscopic molecular systems remain key challenges for understanding intermolecular quantum effects in chemistry. Here, we study the quantum Fisher information, as a multipartite entanglement witness. We generalize the entanglement witness functional related to quantum Fisher information regarding nonidentical local response operators. We demonstrate its effectiveness for intermolecular entanglement in ultrastrong light-matter coupling in cavity quantum electrodynamics, including near the superradiant phase transition. Additionally, we establish a connection between quantum Fisher information and the dipole correlator, indicating that entanglement could be detected through absorption spectroscopy. Our work proposes a general protocol to detect intermolecular entanglement in chemical systems at room temperature.
CRIS-Team Scopus Importer:2025-08-15